Relationship between eye behaviour during conceptual stage design process and the level of creativity - Y. M., Fadzli (UTM, 2016)
In the past few years, several experiments in cognitive science, human-computer interaction, and marketing research impressively showed that eye tracking is a powerful research method to gain deeper insights into human behavior. In Engineering Design field, various studies have been conducted in attempt to understand creativity in design process. However, up to date only a small number of eye tracking experiments has been conducted in engineering design field. The focus of this research is to determine the relationship between designer’s eye behavior parameters and different creativity level of designers based on its design output. This experiment explored three fundamental eye behavior parameters:fixation count, fixation time and saccades. They were meaningful in understanding the cognition of designers during ideation stage in designing process. The results show that creative designers tend to have shorter fixation time, and higher fixation and saccades counts. These indicate that the creative designers immediately absorbed the task assigned and perform multiple sketching process simultaneously.